ANALISIS RELEVANSI INFORMASI, RELIABILITAS, DAN ASIMETRI INFORMASI SETELAH PENGADOPSIAN IFRS (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2014) - Anggraini, Shella Yolan; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The objectives of the research are to examine the impact of adoption of IFRS in Indonesia on quality of financial statement information in terms of relevance and reliability and to examines information asymetry. The Relevance is measured by combined value relevance of book value of equity and net income, reliability is measured by absolute discretionary accrual as an inverse measure, and information asymetry is measured by bid ask spread. Data were collected from the financial statements of the manufacture companies that listed at Indonesia Stock Exchange. Research conduct in 6 years (2009-2014). By using purposive sampling and balanced panel data, there are 31 companies fulfilling the sample criteria. Multiple linier regression and paired sample t-test model is used to test the hypothesis. The results showed that there is an increasing quality of financial statement information after the adoption of IFRS but no difference in information asymmetry after the adoption of IFRS